Long-term follow-up of antithrombotic management patterns in acute coronary syndrome patients - Fatih Sinan Ertaş; Lale Tokgozoglu; On Behalf Of The Epicor Study Group (KARE Publishing, 2018)
Objective: The aim of this study was to evaluate the long-term, post-discharge follow-up of antithrombotic management patterns (AMPs), clinical outcomes, and real-life health status of patients hospitalized acute coronary syndrome (ACS). Methods: A total of 1034 patients hospitalized for ACS within 24 hours of symptom onset who survived to discharge were included. Of those, 514 had ST-segment elevation myocardial infarction (STEMI) and 520 had unstable angina (UA)/non-STEMI (NSTEMI). Data on follow-up AMPs, clinical outcomes, and health status were collected during 24 months of follow-up. Results: The overall all-cause mortality was 6.4% (6.7% in UA/NSTEMI and 6.0% in STEMI patients), cardiovascular (CV) events had occurred in 9.4% (9.8% in UA/NSTEMI and 8.9% in STEMI patients), and bleeding events in 2.0% (2.3% in STEMI and 1.7% in UA/NSTEMI patients) of patients at 2 years after discharge. EuroQol-visual analogue scales scores increased from 78.9 to 81.6 in STEMI patients, and from 76.0 to 76.2 in UA/NSTEMI patients. Discharge and 2-year post-discharge scores for the EuroQol-5D index were 0.7 and 0.9, respectively in STEMI patients, while it was 0.8 for each period in UA/STEMI patients. Overall, 57.5% of the patients on dual antiplatelet (AP) therapy at discharge remained on this treatment at 2 years after discharge. The use of 1AP/0 anticoagulant (AC) and ≥2AP/0AC were associated with a CV event risk of 10.5% and 8.9%, a mortality risk of 10.5% and 5.8%, and a bleeding event risk of 0.9% and. 2.2%, respectively. Conclusion: These findings in a real-life population of ACS patients emphasize the importance of longer-term follow-up of ACS patients surviving hospitalization and support the likelihood of more favorable long-term outcomes in ACS management with the current treatment practices.